Biologic Therapy Carries a Very Low Risk of Reactivation in Hepatitis B Surface Antigen-Negative Phase of Hepatitis B - Ergenç, İlkay; Kani, Haluk Tarık; Karabacak, Murat; Cömert Özer, Elif; Mehdiyev, Shahin; Jafarov, Fuad; Abacar, Kerem Yiğit; Kutluğ Ağaçkıran, Seda; Sevik, Gizem; Aslan, Rahmi; Alibaz Öner, Fatma; İnanç, Nevsun; et al. (Turkish Journal of Gastroenterology, 2022)
Background: The risk of hepatitis B reactivation in hepatitis B surface antigen-negative phase of hepatitis B virus-infected patients exposed to biologic agents is not clear. We aimed to investigate the reactivation rate in hepatitis B surface antigen-negative phase of hepatitis B virus-infected patients after biologic therapy.Methods: Patients followed at gastroenterology, rheumatology, and dermatology clinics with a diagnosis of immune-mediated inflammatory diseases were screened. Immune-mediated inflammatory diseases patients exposed to biologic agents with a negative hepatitis B surface antigen and positive hepatitis B core immunoglobulin G antibody were included in the study.Results: We screened 8266 immune-mediated inflammatory disease patients, and 2484 patients were identified as exposed to biologic agents. Two hundred twenty-one patients were included in the study. The mean age was 54.08 ± 11.69 years, and 115 (52.0%) patients were female. The median number of different biologic subtype use was 1 (range: 1-6). The mean biologic agent exposure time was 55 (range: 2-179) months. One hundred and fifty-two (68.8%) patients used a concomitant immunomodulatory agent, and 84 (38.0%) patients were exposed to corticosteroids during biologic use. No hepatitis B reactivation with a reverse seroconversion of hepatitis B surface antigen positivity was seen. Antiviral prophylaxis for hepatitis B was applied to 48 (21.7%) patients. Hepatitis B virus-DNA was screened in 56 (25.3%) patients prior to the biologic exposure. Two patients without antiviral prophylaxis had hepatitis B virus-DNA reactivation with a negative hepatitis B surface antigen during exposure to the biologic agent.Conclusion: We found 2 reactivations and no hepatitis B surface antigen seroconversion in our cohort. Antiviral prophylaxis for patients exposed to biologic agents may need to be discussed in more detail.Cite this article as: Ergenç İ, Kani HT, Karabacak M, et al. Biologic therapy carries a very low risk of reactivation in hepatitis B surface antigen-negative phase of hepatitis B. Turk J Gastroenterol. 2023;34(2):156-160.